Analysis of the verses (poetries) of the Qur’an in the text of the treatise of al-Farabi «Usul ‘ilm at-Tabiya» - Paltore, Y.M. (Journal of Oriental Studies, 2021)
Currently according to our research Al-Farabi’s treatise «Makalaat ar-Rafi’a fii usul ‘ilm at-tabiya» has three versions. This treatise was translated into Turkish in 1951 by Turkish scholars Aydin Sayili and Necati Lugal. Despite the fact that this treatise was translated into the Kazakh in 1978, actually its Kazakh translation is not in scientific application. In this treatise, al-Farabi substantiates his main ideas with the verses of the Qur’an and texts from the hadith and emphasizes the cognition of «Adam» (man). Thus, the concepts of «Akl» (mind), «Rukh» (spirit) and «Nafs» are considered separately. To confirm his point of view, al-Farabi quotes verses from the Qur’an. And during interpretation the concepts of «Rukh» and «Nafs» he confirms his theories with religious texts. Thus, al-Farabi’s ideas are closely associated with the content of the Qur’an. This article contains the portries of the Holy Qur’an quoted in the text of the treatise of Abu Nasr alFarabi «Usul ‘ilm at-Tabiya» and analyzes their Kazakh translations and arguments. Key words: al-Farabi, manuscript, Usul ‘ilm at-Tabiya, original text, translation, verses of the Qur’an.